Preventive Measures in Patients with Central Serous Choroidopathy with Optic Disc Hypoplasia (Eurasian Scientific Herald, 2023)
Purpose of the study Evaluation of the effectiveness of the method for the prevention of central serous choroidopathies in patients with optic disc pit.